Agenda Setting for the 20% Mandatory Subcontracting Policy in Zambia's Construction Sector: The Multiple-Streams Framework. (April 2023) - Tembo, Sydney; Lim, Seunghoo
Agenda setting is critical to public policy due to impacts on subsequent policy processes. On July 25, 2012, the Zambian Government issued a policy pronouncement directing the Road Development Agency to apply a 20% mandatory subcontracting to all road contracts valued above ZMW30 million. The policy directive aimed to improve the capacity of local contractors, create jobs and address concerns of declining local participation due to the dominance of foreign contractors. This pronouncement triggered the implementation of a policy initiative based on road subsector guidelines, but several studies have reported implementation challenges. Applying the multiple-streams framework, this study identifies both the failure of agenda setting to lead to policy formulation and the fragmentation of the construction sector policy community as initial sources of implementation challenges. The study recommends revisiting agenda setting and conducting research on defragmenting the construction policy community.